Geochronologically constrained life cycles of telescoped porphyry-epithermal systems at the La Arena district, Northern Peru - Santos Polo, Alan Humberto (2023)
La Arena and Alizar are porphyry-type Cu-Au-(Mo) deposits with associated Calaorco and Vanessa high-sulfidation epithermal mineralizations, respectively. In this study, we conducted multiple conventional geochronologic analyses on samples from La Arena district, with the objective to obtain precise a temporal relationship among porphyry emplacement, hydrothermal alterations, cooling, exhumation history and preservation, together with published age data for the district. A precursor quartz–diorite pluton and a late–mineral andesite porphyry bracketed the mineralization in the La Arena and Alizar porphyry deposits. Zircon U-Pb dating of these intrusive rocks display markedly concordant ages, with emplacement beginning and ending at 26.50 ± 0.23 to 25.36 ± 0.07 Ma at La Arena, and at 26.47 ± 0.08 to 25.30 ± 0.07 Ma at Alizar. 40Ar/39Ar chronologic data for hydrothermal biotite from the potassic zone ranges from 25.97 ± 0.16 to 25.73 ± 0.16 Ma in the Alizar, and hypogene alunite from the advanced argillic alteration yield an age of 25.66 ± 0.15 Ma in the Vanessa. The weighted mean apatite (U–Th)/He ages of the porphyry intrusions of the La Arena and Alizar range from 24.26 ± 0.56 to 23.42 ± 0.37 Ma. These geochronologic data reveal that the porphyry systems were emplaced intermittently for at least 1.2 m.y. during the late Oligocene (26.5 – 25.3 Ma). The porphyry intrusions would have been uplifted from its depth of formation at ~ 2 km suggested by telescoped and a short time period (0.07 m.y.; 40Ar/39Ar ages) between porphyries and associated high-sulfidation epithermal events. The cooling history from zircon crystallization at 800 ◦C to thermal collapse at 75 ◦C (apatite helium close temperature) lasted ~ 2.5 m.y. in the ore-systems. The thermal collapse occurred coeval with the Inca IV orogeny (~24 Ma), period of rapid uplift and exhumation in northern Peru (0.24 km/m.y.; (U-Th)/He age-elevation spectrum). If exhumation continued at the rate of 0.24 km/m.y. unroof of the ore-deposits lasted 5 m.y. (24–19 Ma). Since their exposure at ~ 19 Ma, these ore deposits were subjected to weathering and oxidation during 2.12 m.y. It is thus estimated that approximately 500-m thickness of materials have been removed from the Alizar and La Arena during uplift and erosion, including a large volume of ore. Subsequent volcanic activity occurred during the Quechua I orogeny (~17 Ma) at ca. 16.88 Ma, leading to burial and partially preservation of these ore deposits.